DEVELOPMENT OF AN EQUIPMENT FOR CRUSHING GREEN COCONUT - Simonetti, R. H.; Guimarães, M. S.; Pinto, J. S.; Silva, M.; Nääs, I. de A. (Revista Brasileira de Engenharia de Biossistemas, 2017)
Brazil accounts for about 80% of South America’s production of coconuts. The residue of coconut husks becomes an environmental problem since its degradation can occur in up to eight years. On the other hand, processed fibers can be transformed into a series of products used in the construction, automotive and agricultural inputs or gardening industries. The processing of extracting the fibers from green or dried coconut is a difficult task that demands hard work. The mechanization of the process is needed in the sense of improving the quality of life of the worker of this segment, facilitating the further use of the fibers, and reducing the environmental impact of the product. This study aimed to develop a coconut shell crusher. The principle of operation of the coconut crusher was based on the rotor drive of the knives that performs the process of cutting the coconuts and deposited in the crusher. Aiming to obtain a simple and practical equipment, so that the crushing is executed without risk. Compression tests were performed to determine the breaking strength of the fruit and also calculated the values that should have the motor torque to be used. The prototype was built and tested. In the trial the coconuts were mostly completely crushed, indicating the efficiency of the machine. The mechanization of part of the processing of obtaining coconut fibers can be a major advance in areas of large deposits of this material, in the sense of improving the worker’s quality of life in the sector, as well as reducing the environmental impact of this material, improving the further use of the fibers.